Design of an Onshore Wave Energy Converter Device for Electricity Generation - Sangar, S.; Thiruvaran, T.; Aravinthan, V.; Thanatheeban, B. (IESL, 2021)
Demand for renewable energy is growing faster due to its cleaner nature. Sri Lanka is blessed with renewable energy sources and, currently renewable electricity is mainly produced from hydro power, Solar and Wind. Since, Sri Lank is surrounded by sea; it has huge Sea Wave energy potential and can be harnessed in the future. Wave Energy Converters (WEC) are the devices, which are used to produce electricity using sea wave energy. Wider range of WEC prototypes have been presented worldwide. However, most of the technologies are still at research level because they are expensive and practically challenging. Oscillating Water Column type WEC are matured technology and installed in few places but, they require very high initial investment and big in size becausea huge air chamber in the device. This paper contains description and the laboratory results of a scale model of a new shoreline Wave energy Converter. It has many advantages such easy to build, less maintains is required and moving parts (DC generator) are isolated from sea water. Where the proposed device contains three major parts those are single acting pneumatic pump, Air storage tank and a turbine coupled with DC generator. Sea Wave is used to drive the single acting cylinder which will pump the airinto the storage tank. Then the air is used to rotate the turbine. Finally the DC generator will produce electricity. This prototype device could generate 15W peak power across 25 ohm load when the air storage tank pressure is 3.2 bars. It can produce huge power when we scale up the device. Also, proposed device can be used to harness wave energy by installing at onshore. Future works can be done to analyse the proper mooring system.
Keywords: Renewable Energy; Sea wave energy; Wave Energy Converters; Scale model device; Onshore device